KAITAN ANTARA TINGKAT PENGETAHUAN IBU DAN TINGKAT KEKAMBUHAN EPILEPSI DENGAN KUALITAS HIDUP PASIEN EPILEPSI ANAK DI RUMAH SAKIT UMUM DAERAH DOMPU - Iing, Iing; Omy Aulia Syabiani; I Wayan Tunjung; Ni Made Yuli Artini (Nusantara Hasana Journal, 2025)
Epilepsy contributes to a significant burden of disease in children and adolescents worldwide. The study aims to determine the relationship between maternal knowledge, duration of suffering and epilepsy recurrence rate with the quality of life of pediatric epilepsy patients at Dompu Regional General Hospital. This study is an observational analytical study with a cross-sectional study design. This study was conducted in August 2024 at Dompu District Hospital, West Nusa Tenggara Province. There is a significant relationship between maternal knowledge and epilepsy recurrence rate on the quality of life of pediatric epilepsy patients at Dompu Regional General Hospital. There is a significant relationship between maternal knowledge and epilepsy recurrence rate on the quality of life of epilepsy patients at Dompu Regional General Hospital which is indicated by a p-value of 0.011 (p-value <0.05) and a correlation coefficient of 0.370, which indicates that the higher the mother's knowledge, the better the child's quality of life. There is a significant relationship between the rate of epilepsy recurrence and the quality of life of epilepsy patients at Dompu Regional General Hospital, which is indicated by a p-value of 0.019 (p-value <0.05) and a correlation coefficient of -0.344, which indicates that the more frequent the recurrence occurs, the lower the patient's quality of life.